1984
DOI: 10.1126/science.6691151
|View full text |Cite
|
Sign up to set email alerts
|

Salt Taste Transduction Occurs Through an Amiloride-Sensitive Sodium Transport Pathway

Abstract: An important early event in mammalian gustatory transduction with respect to sodium chloride has been found to be the passage of sodium ions through specific transport pathways in the apical region of the taste bud. The inward current caused by sodium chloride placed on the mucosal surface of an in vitro preparation of rat dorsal lingual epithelium can be substantially reduced by the blocker of sodium ion transport, amiloride. The data show (i) that amiloride is a specific blocker of the chorda tympani respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
231
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(246 citation statements)
references
References 10 publications
13
231
0
1
Order By: Relevance
“…A seminal finding was published by Heck et al [38] in 1984 when they reported that Na + permeates cation channels in taste cells, specifically, amiloride-sensitive ENaCs (similar to those found in the kidney) on the anterior tongue. Passive Na + influx through ion channels, driven by the presence of Na salts in the stimulus (that is, a Na + concentration gradient favoring Na + influx), would depolarize and thereby excite taste receptor cells.…”
Section: Salty Chemosensory Transductionmentioning
confidence: 99%
“…A seminal finding was published by Heck et al [38] in 1984 when they reported that Na + permeates cation channels in taste cells, specifically, amiloride-sensitive ENaCs (similar to those found in the kidney) on the anterior tongue. Passive Na + influx through ion channels, driven by the presence of Na salts in the stimulus (that is, a Na + concentration gradient favoring Na + influx), would depolarize and thereby excite taste receptor cells.…”
Section: Salty Chemosensory Transductionmentioning
confidence: 99%
“…In rodents, treating the anterior tongue with amiloride, an epithelial Na + channel blocker, disrupts performance on sodium discrimination tasks (Spector et al, 1996) and inhibits chorda tympani responses to NaCl (Heck et al, 1984). Consequently, it is believed that sodium taste is transduced via the influx of Na + through epithelial sodium channels (ENaC) in the anterior tongue.…”
Section: Peripheral Gustatory Processingmentioning
confidence: 99%
“…All solutions of glutamate agonists were titrated to pH 6.0-7.0 to avoid potential complications introduced by acid taste. Also, all solutions, including water, contained 30 pM amiloride to minimize the contribution of Na+ taste (Heck et al, 1984;Yamamoto et al, 1991;Gilbertson and Gilbertson, 1994). Half of the rats for each taste stimulus were injected intraperitoneally with 0.3 M LiCl (at 1 ml/100 gm body weight).…”
Section: Methodsmentioning
confidence: 99%